A Clinico-Pathological Study on Amlapitta w.s.r to Gastroesophageal Reflux Disease (GERD) and its Comparative Management with Narikela Khanda and Kusmanda Khanda. - Rout, Diptimayee; Panda, P K; Nayak, Utkalini; Biswal, Ambuja Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Amlapitta described in Ayurveda classics resembles to the clinical features of GERD. Amlapitta is more prevalent disease of Annavaha Srotasa (gastrointestinal system) described in various classical Ayurvedic texts. Narikela Khanda and Kushmanda Khanda are the formulations mentioned in Bhaisajya Ratnavali indicated for management of Amlapitta. Aims: To evaluate the effect of Narikela Khanda and Kushmanda Khanda in management of Amlapitta. Materials and methods: A non-randomized, single-armed, open-labeled clinical trial was conducted in 30 patients having classical symptoms of Amlapitta, administered with 10gm of Narikela Khanda & 10gm of Kushmanda Khanda twice a day after food for 30 days respectively. The assessment was done based on subjective parameters, i.e., Amlodgara (sourbelching), Daha (heartburn), Gaurava (heaviness), Utklesha (nausea), A vipaka (indigestion) and Aruchi (loss of appetite) were taken into consideration. The subjective parameters were analysed by Wilcoxon-W test and p-value. Result- In Group A, 6.67% patients had marked improvement, while 73.33% patients had moderate improvement and 20.00% mildly improved. In Group B, 60.00% patients had moderate improvement and 40% marked improved. In both the Group the result was statistically significant, but improvement was noticed more in Group- B. Conclusion- On comparison between two groups, Kushmanda Khanda have shown more effect than Narikela Khanda. No adverse effects were noticed during clinical trial in both groups.